The influence of different protective agents on survival of Lb. salivarius i24 subjected to freeze-drying for production of live cell in powderized form - Lim, Chin Ming; Arbakariya, Arbakariya; Ho, Yin Wan; Raha, Raha (Penerbit Universiti Sains Malaysia, 2004)
The use of probiotic microorganisms for food and pharmaceutical industries is mainly driven by the increasing consumer health awareness.